2009
DOI: 10.1016/j.tet.2008.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed desulfinylative C–C allylation of Grignard reagents and enolates using allylsulfonyl chlorides and esters

Abstract: a b s t r a c t 2-Methylprop-2-ene-, prop-2-ene-, 1-methylprop-2-ene-, and (E)-but-2-enesulfonyl chlorides have been used as electrophilic partners in desulfinylative palladium-catalyzed C-C coupling with Grignard reagents and sodium salts of dimethyl malonate and methyl acetoacetate. Neopentyl alk-2-ene sulfonates can also be used as electrophilic partners in desulfinylative allylic arylations and allylic alkylations. The regioselectivity of the allylic arylation and alkylation depends on the nature of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 122 publications
1
14
0
Order By: Relevance
“…2-Butene-1-sulfonyl Chloride (3): [35] Using the same procedure as that used for 1, starting from 1-butene (2.0 g, 35. 3-Butene-2-sulfonyl Chloride (4): [9] Using the same procedure as that for 1, starting from 2-butene (2.0 g, 35. , dried through a column packed with phosphorus pentoxide and aluminum oxide, was transferred on the vacuum line to the CH 3 CN solution frozen at -196°C. The mixture was allowed to melt and to warm to -40°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2-Butene-1-sulfonyl Chloride (3): [35] Using the same procedure as that used for 1, starting from 1-butene (2.0 g, 35. 3-Butene-2-sulfonyl Chloride (4): [9] Using the same procedure as that for 1, starting from 2-butene (2.0 g, 35. , dried through a column packed with phosphorus pentoxide and aluminum oxide, was transferred on the vacuum line to the CH 3 CN solution frozen at -196°C. The mixture was allowed to melt and to warm to -40°C.…”
Section: Methodsmentioning
confidence: 99%
“…gave the product (58 mg, 56 %) as a light yellow oil. 1 1-(But-2-enyl)-2-methylbenzene [9] and 1-(But-3-en-2-yl)-2-methylbenzene (Table 4, Entries 1 and 4) [9] Method A: Following the typical experimental procedure, sulfonyl chloride 3 (0.1 g, 0.65 mmol, 1 equiv.) and o-tolylmagnesium chloride (5a; 1.0  in THF, 1.0 mL, 1.0 mmol, 1.5 equiv.)…”
Section: Typical Experimental Procedures For the Iron-catalyzed Desulfmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] We have also shown that 2-methylprop-2-ene-(1), prop-2-ene-(3), and (E)-but-2-enesulfonyl chlorides (4) are useful electrophilic partners in desulfinylative palladium-catalyzed C À C coupling reactions with inexpensive Grignard reagents and sodium salts of malonic esters and methyl acetoacetate. [9] As these sulfonyl chlorides can be prepared in one-pot operations (Scheme 1) through a BCl 3 -promoted ene reaction of the corresponding monoalkenes with sulfur dioxide, [10] substrates 1-4 have become powerful electrophilic allylating agents (without BCl 3 , the ene reaction of simple monoalkenes with SO 2 is endergonic above À100 8C). [11] We have recently reported that iron catalysts can be used in the desulfinylative CÀC cross-coupling reaction of Grignard reagents with alkane-, alkene-, and arenesulfonyl chlorides [12] and with alk-3-enesulfonyl chlorides.…”
mentioning
confidence: 99%
“…Since we have previously observed that alk-2-enesulfonyl chlorides undergo fast desulfinylation in the presence of palladium complexes, [9] generating electrophilic allylpalladium intermediates, we searched for reducing agents capable of converting these into C-nucleophiles (all-A C H T U N G T R E N N U N G ylation by umpolung [24] ). Our results are summarized in Table 1 for the reaction of 1 with benzaldehyde to give 7 a.…”
mentioning
confidence: 99%